2020
DOI: 10.1101/2020.04.10.029454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of a novel SARS-CoV-2 sub-genomic RNA due to the R203K/G204R variant in nucleocapsid: homologous recombination has potential to change SARS-CoV-2 at both protein and RNA level

Abstract: The COVID-19 pandemic is caused by the single-stranded RNA virus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a virus of zoonotic origin that was first detected in Wuhan, China in December 2019. There is evidence that homologous recombination contributed to this cross-species transmission. Since that time the virus has demonstrated a high propensity for human-to-human transmission.Here we report two newly identified adjacent amino acid polymorphisms in the nucleocapsid at positions 203 and 204… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 54 publications
3
55
0
1
Order By: Relevance
“…Our results also showed that some mutations were widely distributed, and their occurrence rates had different dynamic fluctuations. Take R203K/G204R in N as an example, this mutation combination with increased incidence was found mainly in Europe till March 2020 [39,40], while our data showed its high frequency was also in Asian countries as of July 2020, suggesting that these two mutations might be conducive to SARS-CoV-2 adaptability and spread. Therefore, it is particularly important to pay attention to the difficulties in COVID-19 diagnosis and treatment that probably caused by these mutations, especially in countries with high occurrence rates.…”
Section: Orf3a-s Complexes But Weaker Affinities In G251v Orf3a-m Anmentioning
confidence: 53%
“…Our results also showed that some mutations were widely distributed, and their occurrence rates had different dynamic fluctuations. Take R203K/G204R in N as an example, this mutation combination with increased incidence was found mainly in Europe till March 2020 [39,40], while our data showed its high frequency was also in Asian countries as of July 2020, suggesting that these two mutations might be conducive to SARS-CoV-2 adaptability and spread. Therefore, it is particularly important to pay attention to the difficulties in COVID-19 diagnosis and treatment that probably caused by these mutations, especially in countries with high occurrence rates.…”
Section: Orf3a-s Complexes But Weaker Affinities In G251v Orf3a-m Anmentioning
confidence: 53%
“…We designed a tool, periscope (https://github.com/sheffield-bioinformatics-core/periscope), to re-analyse raw data from SARS-CoV-2 isolates to identify sgRNA based on the detection of the leader sequence at the 5' end of reads as described previously (Leary et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Non-Canonical Sub-Genomic RNA In addition to estimating sgRNA for known ORFs, we can use periscope to detect novel, non-canonical sgRNA (Figure 4). We previously applied periscope to detect one such novel sgRNA (N*) which is a result of the creation of a new TRS site by a triplet variation at position 28881 to 28883 which results in production of a truncated N ORF (Leary et al 2020). To classify sgRNA as non-canonical, supporting reads must fulfil two criteria; First, the start position does not fall in a known TRS-B region (+/-20bp from the leader junction), and second, in ONT data the start position must not fall within +/-5bp from a primer sequence.…”
Section: Lower Limit Of Detectionmentioning
confidence: 99%
“…D614G (Aspartate to Glycine) mutation in the S gene has been reported to result in increased transduction into human epithelial cells ( Daniloski et al, 2020 ). N gene mutations R203K and G204R are believed to increase viral fitness, survival and adaptation to humans ( Leary et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%